Antibacterial coating of tooth surface with ion-releasing pre-reacted glass-ionomer (S-PRG) nanofillers. Issue 2 (February 2021) - Mayumi, Kayoko; Miyaji, Hirofumi; Miyata, Saori; Nishida, Erika; Furihata, Tomokazu; Kanemoto, Yukimi; Sugaya, Tsutomu; Shitomi, Kanako; Akasaka, Tsukasa
Abstract: Objectives: Surface pre-reacted glass-ionomer (S-PRG) fillers release antibacterial borate and fluoride ions. We fabricated nanoscale S-PRG fillers (S-PRG nanofillers) for antibacterial coating of tooth surfaces and assessed the antibacterial effects of this coating in vitro. In addition, we creating a canine model of periodontitis to evaluate the effectiveness of S-PRG nanofiller application on tooth roots and improvement of periodontal parameters. Methods: Human dentin blocks were coated with S-PRG nanofiller (average particle size: 0.48 μm) and then characterized by scanning electron microscopy (SEM), energy dispersive X-ray spectrometer (EDX), and ion-releasing test. Antibacterial effects of dentin blocks coated with S-PRG nanofiller were examined using bacterial strains, Streptococcus mutans and Actinomyces naeslundii. Next, we created an experimental model of periodontitis in furcation of premolars of beagle dogs. Then, S-PRG nanofiller coating was applied onto exposed tooth root surfaces. Periodontal parameters, gingival index (GI), bleeding on probing (BOP), probing pocket depth (PPD), and clinical attachment level (CAL), were measured from baseline until 4 weeks. In addition, bone healing was radiographically and histologically examined. Results: SEM and EDX revealed that S-PRG nanofillers uniformly covered the dentin surface after coating. Dentin blocks coated with S-PRG nanofiller showed ion-releasing property, bacterial growth inhibition, and sterilization effects. In the experimental periodontitis model, S-PRG nanofiller coating significantly reduced clinical inflammatory parameters, such as GI (P < 0.01) and BOP (P < 0.05), compared to uncoated samples. In addition, PPD and CAL significantly decreased by S-PRG nanofiller coating (2 weeks: P < 0.05; 3 and 4 weeks: P < 0.01), suggesting the improvement of periodontitis. Micro-CT and histology revealed that bone healing of furcation defects was enhanced by S-PRG nanofiller coating. Conclusion: S-PRG nanofiller coating provides antibacterial effects to tooth surfaces and improves clinical parameters of periodontitis. Abstract : Actinomyces naeslundii ; Animal model; Antibacterial activity; Anti-inflammatory; Class II furcation defect; Ion-releasing; Periodontitis; Root dentin; Streptococcus mutans ; Surface pre-reacted glass-ionomer (S-PRG) filler.